Significance of obstructive sleep apnea in the patient with pulmonary hypertension. Issue 6 (November 2015) - Minic, Milan; Ryan, Clodagh M.
Abstract : Purpose of review: The purpose of this review was to evaluate the consequence of obstructive sleep apnea (OSA) in pulmonary hypertension by reviewing the current literature and understanding potential pathophysiological mechanisms. Recent findings: Small studies have suggested a high prevalence of comorbid OSA in those with known pulmonary hypertension. Pathophysiological mechanisms are highly suggestive of potential deleterious effect of OSA on pulmonary hemodynamics. Summary: Clearly, current research work on comorbid OSA and pulmonary hypertension is still in its infancy and the field is ripe for future investigation. The significance of OSA in this population has yet to be fully determined.